Power Synthesis of Mask-Constrained Shaped Beams Through Maximally-Sparse Planar Arrays - Andrea Francesco Morabito (Universitas Ahmad Dahlan, 2016)
A new approach to the optimal synthesis of planar arrays able to radiate mask-constrained shaped beams by exploiting the minimum number of radiating elements is presented. By taking advantage from both the recent theory of Compressive Sensing and the multiplicity of equivalent solutions available for the generation of an unique shaped-beam power pattern, the synthesis results extremely fast and effective. In particular, the overall design is reduced to a Convex Programming optimization, with the inherent advantages in terms of solutions’ optimality and computational burden.